1999
DOI: 10.2337/diacare.22.3.484
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia is a risk factor for coronary arteriosclerosis in Japanese patients with type 2 diabetes.

Abstract: There seems to be a clear relationship between hyperhomocysteinemia and an increased risk of coronary arteriosclerosis in Japanese patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 0 publications
0
44
1
1
Order By: Relevance
“…Several studies have demonstrated that Hcy levels are increased in diabetes. Elevated Hcy levels were shown to be a stronger risk factor in diabetics than in non-diabetic patients (1,19,20,21,24,29,30). Plasma Hcy levels were also found to be significantly elevated in our type 2 diabetic patients with atherosclerotic vascular disease when compared with patients without vascular disease.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Several studies have demonstrated that Hcy levels are increased in diabetes. Elevated Hcy levels were shown to be a stronger risk factor in diabetics than in non-diabetic patients (1,19,20,21,24,29,30). Plasma Hcy levels were also found to be significantly elevated in our type 2 diabetic patients with atherosclerotic vascular disease when compared with patients without vascular disease.…”
Section: Discussionmentioning
confidence: 49%
“…Hcy levels were found to be elevated in patients with vascular disease and were proposed to contribute to atherosclerosis in patients with coronary artery disease, stroke, and peripheral vascular disease (1,19,20,22,24,28). Hcy-induced vascular pathologies include fragmentation of the internal elastic lamina, disruption of elastic fibers, smooth muscle hyperplasia, and arterial and venous thrombosis (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both clinical and experimental studies have suggested that mild increases in plasma homocysteine may be an independent risk factor for CAD (7,8). A recent study in type 2 diabetes also demonstrated a clear relationship between increased homocysteinemia and increased risk of CAD (9). Hyperhomocysteinemia may be an even stronger risk factor for CAD in subjects with type 2 diabetes than in nondiabetic subjects (10).…”
mentioning
confidence: 96%
“…After removal of unbound proteins by washing of the columns with buffer B (20 mmol/l Tris [pH 7.5], 0.5 mmol/l EDTA, 0.5 mmol/l EGTA, and 10 mmol/l ␤-mercaptoethanol), fractions containing PKC were eluted with buffer C (Tris [pH 7.5], 0.5 mmol/l EDTA, 0.5 mmol/l EGTA, 10 mmol/l ␤-mercaptoethanol, and 0.2 mol/l NaCl). Eluates were analyzed for PKC activity, following the optimum conditions of the assay, by measuring the incorporation of 32 P into the synthetic peptide Ac-myelin basic protein (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The specificity of the assay was determined by subtracting the radioactivity obtained in the presence of the pseudosubstrate inhibitor PKC(19-36) from total radioactivity.…”
mentioning
confidence: 99%